Magnetic properties of rare-earth hydrazone compounds - Guskos, N.; V. Likodimos; Glenis, S.; Typek, J.; Wabia, M.; Paschalidis, D.G.; Tossidis, I.; Lin, C.L. (Journal of Magnetism and Magnetic Materials, 2004)
The magnetic properties of two series of trivalent rare earth (R 3+) molecular complexes with hydrazone ligands (R=Ce, Pr, Dy, Ho, Er), adopting different crystal structures, have been investigated by static susceptibility measurements. At high temperatures, the magnetic response is dominated by the paramagnetic contribution of R3+ ions determined by the crystal-field interaction. At low temperatures (T<4K), an antiferromagnetic deviation is observed, most pronounced for the series with the heavier R3+ ions. © 2004 Elsevier B.V. All rights reserved.